ANALISIS SEMIOTIKA DAN PESAN SOSIAL PADA IKLAN COCA-COLA VERSI AVATAR - Nichi Hana Karlina (Universitas Informatika dan Bisnis Indonesia, 2018)
The focus of the study is the Semiotic Analysis of the Coca-Cola Ad Avatar version of a hidden message about social concern about the impact of technological developments that have transformed society into anti-social. To support this research the author uses the theory of Charles Sander Pierce which classifies the type of sign based on objects into three types, namely icon, index and symbol. With Pierce's theory the significance of the signs contained in the Coca-Cola Avatar Version ads will be analyzed. The type of research used is descriptive qualitative research with semiology communication approach. The data of this research is qualitative data so that the data is substansif category which then interpreted with reference of scientific references. Coca-Cola Company also wants to convey the information that in this era of globalization / millenial era, many social concepts, such as integration, unity, nationalism and solidarity, seem to be losing their social reality owing to the excessive use of technological devices. The various social realities that develop on a global scale, especially as a result of advances in information technology, leads to social end. Key Word : Advertisement, Coca-Cola, Avatar, hyperreality